The New Encyclopedia of Southern Culture : Volume 20: Social Class - Hargis, Peggy Griffith, 1955-; Griffin, Larry J. (Book collections on Project MUSE., 2012)
This volume of The New Encyclopedia of Southern Culture offers a timely, authoritative, and interdisciplinary exploration of issues related to social class in the South from the colonial era to the present. With introductory essays by J. Wayne Flynt and by editors Larry J. Griffin and Peggy G. Hargis, the volume is a comprehensive, stand-alone reference to this complex subject, which underpins the history of the region and shapes its future. In 58 thematic essays and 103 topical entries, the contributors explore the effects of class on all aspects of life in the South--its role in Indian remova.